KEUNGGULAN BERSAING DENGAN PENERAPAN FINANCIAL TEKNOLOGY DALAM PERKEMBANGAN UMKM DI ERA SOCIETY 5.0 - Sianipar, Ruth Tridianti; Putri, Juan Anastasia; Nainggolan, Christine Dewi; Siregar, Robert Tua; silitonga, hery pandapotan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The aim of this research is to determine the role of competitive advantage in mediating the relationship between financial technology and financial literacy on the development of MSMEs in Pematang Siantar City. This research method uses a research design with a qualitative approach. The subjects of this research are MSMEs located in each sub-district in the districts of East Siantar, West Siantar, North Siantar, South Siantar, Siantar Marihat, Siantar Martoba, Siantar Sitalasari, Siantar Marimbun. Data collection techniques use observation, interviews, questionnaires and documentation. The data analysis method used is Partial Least Square (PLS). The data analysis test tool uses Smartpls statistical software. The research results obtained: The results of the first hypothesis test (H1) show that financial technology has a positive effect on competitive advantage. The results of the second hypothesis test (H2) show that financial literacy has an effect on competitive advantage. The results of the third hypothesis test (H3) show that the development of MSMEs has an effect on superiority compete